2020
DOI: 10.26822/iejee.2020562133
|View full text |Cite
|
Sign up to set email alerts
|

More Evidence that Math Anxiety is Specific to Math in Young Children: The Correlates of the Math Anxiety Questionnaire for Children (MAQC)

Abstract: Although interest in math anxiety in young children has recently increased, the results of previous studies on math anxiety correlates are inconsistent. The article presents the results of two studies conducted among early school-age learners (6-11 years) where the Math Anxiety Questionnaire for Children (MAQC) was used. The results indicate that the MAQC score (a) positively and moderately/strongly correlates with math anxiety scores obtained with other scales, (b) positively and mainly moderately correlates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
0
9
0
3
Order By: Relevance
“…In a study conducted in the United States by Ramirez et al (2013), they discovered that math anxiety negatively affected students' math achievement as young as grades one and two. Two other studies, one by Mutlu (2019) and another by Szczygieł (2020), also revealed that student achievement and self-esteem in math reduced in those individuals who experienced math anxiety.…”
Section: Math Anxietymentioning
confidence: 86%
See 1 more Smart Citation
“…In a study conducted in the United States by Ramirez et al (2013), they discovered that math anxiety negatively affected students' math achievement as young as grades one and two. Two other studies, one by Mutlu (2019) and another by Szczygieł (2020), also revealed that student achievement and self-esteem in math reduced in those individuals who experienced math anxiety.…”
Section: Math Anxietymentioning
confidence: 86%
“…Several studies indicated that student math anxiety had a negative impact on math achievement (Donolato et al, 2020;Gunderson et al, 2017;Justicia-Galiano et al, 2017;Ramirez et al, 2013;Passolunghi et al, 2020;Szczygieł, 2020). In a large meta-analysis of 131 empirical studies, Namkung et al (2019) discovered that math anxiety and math performance were negatively related in primary and secondary school students.…”
Section: Student Math Anxietymentioning
confidence: 99%
“…A ansiedade matemática sentida pelos alunos está relacionada com o receio destes cometerem erros, terem más notas, receberem feedback negativo por parte dos professores, especialmente quando este ocorre em frente aos seus pares (Lu et al, 2021;Szczygieł, 2020a).…”
Section: Causas Socioambientaisunclassified
“…Relativamente à idade do surgimento da ansiedade matemática para cada género, não existe um consenso na literatura, sendo que as evidências são bastante variadas (Ramirez et al, 2018). Enquanto existem estudos que não encontraram diferenças de género ao nível do primeiro ciclo do ensino básico (Levy et al, 2021), existem também estudos onde estas estão presentes neste nível educativo (Szczygieł, 2020a). Vários estudos apontam para a existência ou para o exacerbamento destas diferenças a partir do ensino secundário (Levy et al, 2021;Milovanović, 2020;Xie et al, 2019).…”
Section: O Género E a Ansiedade Matemáticaunclassified
“…In recent years, there has been a decline in the number of students graduating from the STEM eld of education and one of the possible reasons for that is the rising anxiety levels (Wei & Maat, 2020). Poor math skills lead to lower con dence levels, leading to higher anxiety levels, subsequently resulting in avoidance and underperformance in the STEM domains (Daker et al, 2021).Math anxiety is a predictor of math skills in school children and adults (Szczygieł, 2020). Anxiety affects the well-being of an individual (Devine & Dowker, 2011).…”
mentioning
confidence: 99%